Study on the flame propagation and gas explosion in propane/air mixtures. (15th January 2015) - Liu, Qingming; Zhang, Yunming; Niu, Fang; Li, Lei
Highlights: Laminar burning velocity and Markstein length were studied in a 1.16 m 3 vessel. The variations laminar flame parameters with methane addition have been studied. The flame instability and the critical radii of instability onset were studied. In propane/air flame with an equivalence ratio near 1.8, two explosions take places. Abstract: The characteristics of flame propagations and gas explosions in propane/air mixtures were studied in a 1.16 m 3 explosion chamber with two quartz glass windows of 250 mm diameter. The outward propagations of the spherical flame were recorded by the Schlieren system and high speed motion analysis system. The pressure and temperature histories of the explosion process were measured by pressure sensors and platinum–rhodium thermal couples of 0.02 mm diameter mounted on the wall of the experimental chamber. The instabilities of the propane air flame with different equivalence ratio flame were observed and the critical radii of flame instability onset were obtained. The laminar burning velocities of propane air mixture were obtained by analyzing the experimental results of Schlieren system by using outwardly propagating spherical method. The variation of laminar burning velocity with equivalence ratio was studied. Pressure and temperature responses of the gas explosion were obtained and analyzed. The variations of the maximum overpressure and the maximum temperature with equivalence ratio were obtained and discussed. In propane/air mixture with an equivalence ratio near 1.8, two explosions take places.